Connecting the dots: Understanding the flow of research knowledge within a research brokering network - Rodway, Joelle (Education Policy Analysis Archives, 2015)
Networks are frequently cited as an important knowledge mobilization strategy; however, there is little empirical research that considers how they connect research and practice. Taking a social network perspective, I explore how central office personnel find, understand and share research knowledge within a research brokering network. This mixed methods case study focused on the first two cohorts of school district Mental Health Leaders participating Ontario’s Child and Youth Mental Health program (N=37). Data were collected and analyzed in two phases: 1) the administration of a social network survey to all participants (response rate = 97%), and 2) follow-up interviews with key informants identified by the social network analysis (N=11). The findings indicate that this is a sparse network and the pattern of incoming ties tends to focus on a subset of individuals. When the identified key players (who are sometimes but not always program staff) are removed, network activity is cut by more than half; the removal of the remaining program staff members renders the network virtually non-existent. Research knowledge typically flowed in a single direction as there were few reciprocal ties within the network. Interview data yielded some important insights indicating that participants perceived formal CYMH events as their main access points to research knowledge and that Mental Health Leaders who were identified as prominent sources of research knowledge had pre-existing relationships with CYMH program staff.